Socio-Economic Policy of Latvia: Assessment of Efficiency and Effectiveness - Tsaurkubule, Zhanna; Zhukovskaya, Catherine (Polityka społeczno-gospodarcza Łotwy: ocena wydajności i skuteczności, 2023)
The article presents a scientific and analytical review and defines the essence of the concept of social policy taking into consideration the authors’ version of separation of approaches to the definition of social policy at macro and micro levels, as well as in the context of its connection with economics. A system of indicators for evaluating performance of social policy was developed, and a methodology for evaluating its effectiveness based on a comparative analysis of the dynamics of changes in the main indicators of socio-economic development of Latvia was proposed. The research methodology is based on determining an integral indicator that aggregates eight main areas of socio- -economic policy measured using 32 indicators identified based on expert assessments. The study presents two different approaches to assessing the dynamics of changes in the main indicators of socio-economic development of Latvia for the period from 2010 to 2020. Analysis of the surveyed data showed extremely slow changes in the social well-being of Latvia’s residents, which, however, show positive dynamics, indicating an improvement in Latvia’s overall social policy. The results obtained can be used to monitor the effectiveness of the socio-economic policy (SEP) of Latvia and develop programmes to improve the welfare of the country’s residents.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 87-99
Keywords: Latvia; essence of social policy; assessment of efficiency; Łotwa; istota polityki społecznej; wskaźniki polityki społeczno-gospodarczej; wskaźniki integralne; skuteczność polityki społeczno-gospodarczej; ocena efektywności